2022
DOI: 10.3389/fgene.2022.921972
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and live biotherapeutic products aiming at cancer mitigation and patient recover

Abstract: Molecular biology techniques allowed access to non-culturable microorganisms, while studies using analytical chemistry, as Liquid Chromatography and Tandem Mass Spectrometry, showed the existence of a complex communication system among bacteria, signaled by quorum sensing molecules. These approaches also allowed the understanding of dysbiosis, in which imbalances in the microbiome diversity, caused by antibiotics, environmental toxins and processed foods, lead to the constitution of different diseases, as canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In fact, these microbes have a great deal of dependability when it comes to delaying the beginning of certain illnesses [16,17]. As a result, taking probiotics might offer more affordable options for managing illnesses [18][19][20][21]. Probiotics are recognized to have many health benefits, but it's important to comprehend the processes underlying how they interact with immune cells to promote immunomodulatory effects [22].…”
Section: Figure 1 Influence Of Bifidobacteria On Promoting a Healthy ...mentioning
confidence: 99%
“…In fact, these microbes have a great deal of dependability when it comes to delaying the beginning of certain illnesses [16,17]. As a result, taking probiotics might offer more affordable options for managing illnesses [18][19][20][21]. Probiotics are recognized to have many health benefits, but it's important to comprehend the processes underlying how they interact with immune cells to promote immunomodulatory effects [22].…”
Section: Figure 1 Influence Of Bifidobacteria On Promoting a Healthy ...mentioning
confidence: 99%
“…Many studies have shown that these probiotics are used for therapeutic enhancement and cancer diagnosis. 33,34 Also, milk fat globule membrane (MFGM), whose phospholipid content is negatively correlated with the size, acts as an essential source of dietary delivery of LABs to humans. 35,36 The encapsulation of LAB with MFGM components in infant formula is based on the fact that these components contribute to infants' cognitive development and gut maturation.…”
Section: Exigent Need Of Shifting Toward Precision Probioticsmentioning
confidence: 99%
“…Notably, the integrated approach of genomic sequence analysis and their active involvement in disease control has brought the probiotic therapeutic domain one step closer to clinical recognition. Specifically, involving novel probiotics in cancer management might create a new paradigm in clinical oncology. Many studies have shown that these probiotics are used for therapeutic enhancement and cancer diagnosis. , Also, milk fat globule membrane (MFGM), whose phospholipid content is negatively correlated with the size, acts as an essential source of dietary delivery of LABs to humans. , The encapsulation of LAB with MFGM components in infant formula is based on the fact that these components contribute to infants’ cognitive development and gut maturation . In a recent study, MFGM-coated probiotics have been observed to substantially increase the probiotics’ survival, adhesion, and colonization in the complex digestive system .…”
Section: Exigent Need Of Shifting Toward Precision Probioticsmentioning
confidence: 99%